2012
DOI: 10.1590/s0366-69132012000300018
|View full text |Cite
|
Sign up to set email alerts
|

Processing of red ceramic using a fast-firing cycle

Abstract: This work reports on the processing of red ceramic for civil construction using fast-firing cycles. The firing cycle is an important variable in the processing of red ceramic materials, which contributes to a high consumption of energy. The red ceramic pieces were prepared by industrial extrusion and fired at firing temperatures varying from 700 ºC to 1100 ºC using different firing cycles (slow-firing cycle -1º C/min and fast-firing cycle -10 ºC/min and 20 °C/min). The technological properties (linear shrinkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
8
0
4
Order By: Relevance
“…This value can indeed be modified by slightly changing the raw materials composition, as well as the firing process. Slow-firing cycles, which can reach up to 60 h, are typically used for manufacturing ceramics worldwide [9,36]. The water absorption and porosity have been reported to be higher in the fast-fired clays, while lower linear shrinkage and flexural strength were obtained after low-fired clays [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This value can indeed be modified by slightly changing the raw materials composition, as well as the firing process. Slow-firing cycles, which can reach up to 60 h, are typically used for manufacturing ceramics worldwide [9,36]. The water absorption and porosity have been reported to be higher in the fast-fired clays, while lower linear shrinkage and flexural strength were obtained after low-fired clays [26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by modifying the structural parameters and the magnitude of firing cycles, the quality of the ceramic material can be adjusted [22]. However, it has also been reported that the water absorption in red clay decreases with increasing firing temperature, independently of the firing cycle [36]. Thus, it will be a combination of the speed firing cycle and the firing temperature that will affect the water absorption of ceramic membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the XRD patterns in the Figure with earlier reports [ 38 ] shows that the Naked Clay contains Kaolinite (with 2θ = 12.65°, 25.48°, 40.36° and 55°). Signals for quartz appear (at 2θ 20.70°, 26.69°, 50.26° and 60.11°).…”
Section: Resultsmentioning
confidence: 52%
“…Boas práticas operacionais (BPO): em [52] comprovouse que o processamento de cerâmica vermelha em ciclos de queima rápida (10 e 20 ºC/min) entre 700 e 1100 ºC resulta, para telhas e blocos cerâmicos, propriedades tecnológicas e microestrutura comparáveis àquelas convencionalmente obtidas via queima lenta (1 ºC/min). O ciclo de queima rápida pode ser viável nos âmbitos econômico e técnico, além de trazer benefícios ambientais como a economia de combustível e de energia [52].…”
Section: Mudanças De Matérias-primas Ou Insumos (Mmpi)unclassified
“…O ciclo de queima rápida pode ser viável nos âmbitos econômico e técnico, além de trazer benefícios ambientais como a economia de combustível e de energia [52]. Por conseguinte, entende-se que tal técnica é uma BPO, uma vez que consiste em trazer mudança operacional no processo de queima para reduzir desperdícios de combustível e de energia.…”
Section: Mudanças De Matérias-primas Ou Insumos (Mmpi)unclassified